An Annotated Checklist Of Herpetofauna Of Langkawi Island, Kedah, Malaysia. - Ibrahim, J; Shahrul Anuar, M.S; Norhayati, A.; Shukor, M.N.; Shahriza, S.; Nurul Ain, E.; Nor Zalipah, M.; Mark Rayan, D. (2003)
The herpetofauna ofLangkawi Island was recorded during the Scientific & Heritage Expedition ofthe Langkawi Islands, Kedah from 10 -15 April 2003. The reptiles such as snakes, lizards and turtles and amphibians such as toads and frogs were captured or observed and then identified. The reptiles and amphibians were captured and observed during trekking bouts along used and unused trails, along rivers and streams and during chance encounters